Pediatric Mycosis Fungoides in Singapore: A Series of 46 Children. Issue 4 (29th May 2014) - Heng, Yee Kiat; Koh, Mark Jean Aan; Giam, Yoke Chin; Tang, Mark Boon Yang; Chong, Wei Sheng; Tan, Suat Hoon
Abstract Few studies have evaluated Asian children with mycosis fungoides (MF). We report a series of patients from a tertiary dermatologic institution in Singapore. A retrospective review was performed of patients younger than 16 years old diagnosed with MF between 2000 and 2008 at the National Skin Centre, Singapore. Forty‐six patients were identified. At initial presentation, a provisional diagnosis of MF was made in 19 patients (41.3%), pityriasis lichenoides chronica (PLC) in 11 (23.9%) and postinflammatory hypopigmentation due to eczema or other causes in 11 (23.9%). After skin biopsy, the hypopigmented variant of MF was diagnosed in 42 patients (91.3%). There was one case each of PLC‐like MF, pigmented purpuric dermatosis‐like MF, classic MF, and solitary MF. Pityriasis lichenoides coexisted in three cases (6.5%). All except one patient presented with the early patch‐plaque stage of disease (stage IA/B). The disease did not progress in any of our patients after a mean follow‐up of 71.0 ± 52.5 months. Twenty‐seven patients (58.7%) had complete disease clearance after a mean duration of 27.1 ± 28.1 months; 15 (49.7%) of 32 patients who received narrowband ultraviolet B treatment had complete clearance within an average of 8.9 ± 5.3 months, but 7 patients relapsed within 14.9 ± 14.8 months. One patient with solitary MF failed multiple treatment modalities before eventually achieving disease clearance with photodynamic therapy. Hypopigmented MF is the most common MF variant in Asian children. The diagnostic difficulty is in differentiating this from PLC, which may coexist with MF. Long‐term prognosis is generally favorable.